IMPLEMENTASI VISI MISI BUPATI INDRAGIRI HULU DALAM PENGELOLAAN DESTINASI WISATA DI KABUPATEN INDRAGIRI HULU TAHUN 2022 - Rachman, Gieat Fathur; Handoko, Tito (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Indragiri Hulu Regency is an area that is rich in natural potential, historical value, arts and culture and has a variety of tourism potential that can be developed. The Indragiri Hulu Regency government is also aware of the huge potential of tourist destinations, which is reflected in the Vision and Mission of the Regent of Indragiri Hulu 2021-2026. The Vision of the Regent of Indragiri Hulu 2021-2026 is